جامعہ فتحیہ کی خدمات دینیہ کا مطالعہ (Al-Aasar, 2025)
Jamia Fathia is an ancient religious and educational institution founded in 1875 by a learned and visionary religious scholar, Mian Imamuddin Sahib. This institution is a cradle of knowledge and practice, civilization and education, and sincerity and service, where along with religious knowledge, moral values ​​and principles of practical life are also cultivated. In its century-and-a-half-long history, Fathia University has prepared thousands of students in the academic, intellectual, and spiritual fields, and even today, the institution continues to serve as an exemplary academic center.